2014
DOI: 10.1080/03601234.2014.894780
|View full text |Cite
|
Sign up to set email alerts
|

Tributyltin distribution and producing androgenic activity in water, sediment, and fish muscle

Abstract: This study investigated the concentrations of Tributyltin (TBT) in water, sediment, and fish muscle samples taken from Kaohsiung Harbor and Kaoping River estuary, Taiwan. TBT concentrations in water and sediment samples ranged from less than 18.5 to 34.1 ng Sn L(-1) and from 2.44 to 29.7 ng Sn g(-1) weight per weight (w/w), respectively. Concentrations in the TBT-contaminated fish muscle samples ranged from 10.8 to 79.6 ng Sn g(-1) w/w. The TBT concentrations in fish muscle were higher than those in water and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 28 publications
1
8
0
1
Order By: Relevance
“…For example, TBT was gradually taken up from water and sediment by the crustacean Hyalella azteca over the first 96 h and then reaches steady state after 25-day exposure, with a BCF around 1000 (Bartlett et al 2004). The slow bioaccumulation rate is consistent with the findings of the bioaccumulation rate of TBT in fish larvae, Thymallus (Fent and Looser 1995), and fish muscles (e.g., Megalaspis Vighi and Calamari (1985) cordyla) with a BCF value of 590 to 3263 L kg −1 (Shue et al 2014). In addition, a very low BCF has been reported by Stronkhorst et al (1999) who reported that the BCF of TBT for the heart urchin, Echinocardium cordatum, is only around 200.…”
Section: Bioaccumulation Of Btssupporting
confidence: 80%
“…For example, TBT was gradually taken up from water and sediment by the crustacean Hyalella azteca over the first 96 h and then reaches steady state after 25-day exposure, with a BCF around 1000 (Bartlett et al 2004). The slow bioaccumulation rate is consistent with the findings of the bioaccumulation rate of TBT in fish larvae, Thymallus (Fent and Looser 1995), and fish muscles (e.g., Megalaspis Vighi and Calamari (1985) cordyla) with a BCF value of 590 to 3263 L kg −1 (Shue et al 2014). In addition, a very low BCF has been reported by Stronkhorst et al (1999) who reported that the BCF of TBT for the heart urchin, Echinocardium cordatum, is only around 200.…”
Section: Bioaccumulation Of Btssupporting
confidence: 80%
“…, waterborne concentrations can range from 0 to 163 ng/L downstream of discharge (Svenson and Allard, 2004). The concentration of DHT in the Kaoping river estuary ranges from 0.94 to 3.1 ng/L (Shue et al, 2014). Concentrations of up to 9 ng/L have been found in water discharges in the North Sea (Thomas et al, 2004).…”
Section: Plasma T Plasma E2 Plasma 11ktmentioning
confidence: 98%
“…TBT is a man-made organotin chemical used in the manufacturing of antifouling paints, as a preservative in papers and textiles, in agricultural pesticides, and as a stabilizer in plastic production [21]. TBT easily leaks into the environment [22, 23] and because of its lipophilic nature bioaccumulates in animal [22, 24] and human tissues [25, 26], including the placenta [27] (see Table 1; [25, 28, 29]). To our knowledge, the only available epidemiological study investigating the effects of gestational TBT exposure demonstrated weight gain up to three months of age in newborns with increasing placental TBT concentrations [27].…”
Section: Obesogenic Endocrine Disrupting Chemicalsmentioning
confidence: 99%